Peran Keluarga dalam Membangun Kesadaran Ibadah Pasien Rawat Inap: Sebuah Pendekatan Fenomenologis: Penelitian - Nadila, Ayu; Mahdi, Mahdi; Indra, Syaiful (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to explore the role of families in building religious awareness among patients undergoing treatment at Datu Beru Takengon Regional General Hospital, while also exploring various factors that support or hinder this process during hospitalization. The research method used a qualitative design with a phenomenological approach, involving eight patients and their family members selected purposively, as well as three nurses as additional sources of information. Data were collected through field observations, semi-structured interviews, and documentation, then analyzed using descriptive methods that focused on the dynamics of the experiences of patients and families. The findings revealed that families played a significant role in accompanying patients spiritually, acting as encouragers, reminders of prayer times, and religious motivators during hospitalization. The forms of support provided included reminding patients to pray, assisting with wudu or tayamum, reciting the Qur'an, and strengthening patients' religious motivation. The role of the family has been proven to have a positive impact, such as increasing inner peace, motivation, and awareness of worship in patients. However, this process is not without obstacles, including the physical weakness of patients, the family's limited understanding of worship in sick conditions, and limited visiting hours at the hospital.